Pengaruh E-Money, Tingkat Suku Bunga dan Inflasi Terhadap Jumlah Uang Beredar di Indonesia Tahun 2012 - 2024 - Meidina Indriani; Milla Naeruz; Faty Rahmarisa (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2026)
This study aims to analyze the influence of E-Money, interest rates, and inflation on the money supply in Indonesia during the 2012–2024 period. Managing the money supply plays a crucial role in maintaining macroeconomic stability, especially amidst the rapid innovation of digital payment technologies. The data used in this study are secondary annual time series data sourced from Bank Indonesia and the Indonesian Central Bureau of Statistics (BPS). The analytical method employed is multiple linear regression using SPSS software. The partial results (t-test) show that E-Money has a positive and significant effect on the money supply. Conversely, the interest rate has a negative and significant effect, while inflation also demonstrates a negative and significant influence on the money supply in Indonesia. Simultaneously (F-test), the three independent variables—E-Money, interest rate, and inflation—significantly influence the money supply. The coefficient of determination (R Square) value is 0.908, indicating that 90.8% of the variation in the money supply can be explained by the variables in this research model, while the remaining 9.2% is explained by other factors outside the model.